Validity and reliability of the TargetScan ISSF Pistol & Rifle application for measuring shooting performance - Mon-López, D.; Tejero-González, C. M. (Scandinavian Journal of Medicine & Science in Sports, 2019)
Several technologies, with varying economic costs, are used to measure the performance of Olympic sport shooters, including electronic targets, laser systems, and mobile phone applications. Nevertheless, the International Shooting Sport Federation (ISSF) does not currently accept any mobile applications as valid measurement systems. The objective of the study was to check the validity and reliability of the TargetScan ISSF Pistol & Rifle application, an automatic mobile application for measuring the performance of shooters via image analysis. A total of 1440 shots were fired by 24 shooters (720 shots each for the air rifle and air pistol events), and the target sheets were analyzed with the application installed on an iPhone X. The official competition results and the measurements from the application were then compared. The results showed an almost perfect reliability for air pistol shots (ICC = .999) and no significant differences between the official average scores and those measured by the application. The reliability was also high for air rifle shots (ICC = .998), but the average scores registered by the application were statistically lower than the official results. We concluded that TargetScan ISSF Pistol & Rifle is a low-cost, valid, and reliable application for measuring amateur and semi-professional shooting performance which may be useful to shooters, coaches, clubs, and federations worldwide.